Tracing And Modelling Exchange Rate Volatility In Malaysia - Evan, Lau; Jenny, Yong (EbscoHost, 2015)
This paper traces the presence of currency crises by adopting the exchange market pressure (EMP) index for Malaysia. Our findings confirm several signals of EMP and its impact over the sample period. Besides that, the plots of EMP index allow us witness Malaysia’s quick recovery from these crises through its policy responses. These findings indicate the effectiveness of EMP index as the early warning system in detecting the market pressure of Ringgit Malaysia, especially during the episodes of crises through different exchange rate regimes.